2015
DOI: 10.1515/eces-2015-0035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Irrigation Strategies on Soil Water, Salt, and Nitrate Nitrogen Transport

Abstract: Abstract:Intermittent irrigation has attracted much attention as a water-saving technology in arid and semi-arid regions. For understanding the effect of intermittent irrigation on water and solute storage varied from irrigation amount per time (IRA), irrigation application frequency (IRAF), irrigation intervals (IRI) and even soil texture (ST), intermittent irrigation experiment was carried out in 33 micro-plots in Inner Mongolia, China. The experiment results were used for the calibration and validation of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
1
4
0
1
Order By: Relevance
“…Because the subclay layer in the B-1 column is thick, the infiltration rate for irrigation water is small, and the variation of soil water content at depths of 35 cm and 85 cm (silty sand layer) has a noticeable lag, compared with that at the depth of 5 cm (sub-clay layer). Similar results were concluded in the previous studies [38][39][40][41]. In the B-1 column, the maximum soil water content occurs on the second day of each irrigation period.…”
Section: Water Content Variation In the Soil Columnsupporting
confidence: 91%
“…Because the subclay layer in the B-1 column is thick, the infiltration rate for irrigation water is small, and the variation of soil water content at depths of 35 cm and 85 cm (silty sand layer) has a noticeable lag, compared with that at the depth of 5 cm (sub-clay layer). Similar results were concluded in the previous studies [38][39][40][41]. In the B-1 column, the maximum soil water content occurs on the second day of each irrigation period.…”
Section: Water Content Variation In the Soil Columnsupporting
confidence: 91%
“…Using HYDRUS-ID modeling coupled with a crop growth model for brackish water irrigation, Wang et al [31] found that winter wheat yield decreased by 10% and soil salinity increased above the initial value. Optimal irrigation strategies have also been determined with the joint use of HYDRUS-1D and statistical analysis of soil salt leaching under different irrigation regimes [32]. The objective of this study was to confirm the suitability of long-term irrigation with brackish water.…”
Section: Study Areamentioning
confidence: 99%
“…Nakamura and Kondo, argue the issues related to product life cycles: The researched methods of input-output data endure weakness in conclusions, in continuity of research process that does not consider the natural countenance of the life circle [8]. Regarding the above conceptual facts, we argue that new challenges should stimulate new studies, environmentally safe processes, especially when the standard biogenic composition easily grasp into the groundwater is nitrogen, in the nitrate condition [9,10]. With the objectives towards the exploitation of all resources, in order to provide a better and higher quality of life.…”
Section: Introductionmentioning
confidence: 97%